The central vein sign and its clinical evaluation for the diagnosis of multiple sclerosis: a consensus statement from the North American Imaging in Multiple Sclerosis Cooperative - Sati, Pascal; Oh, Jiwon; Constable, R. Todd; Evangelou, Nikos; Guttmann, Charles R. G.; Henry, Roland G.; Klawiter, Eric C.; Mainero, Caterina; Massacesi, Luca; McFarland, Henry; Nelson, Flavia; Ontaneda, Daniel; et al. (Nature reviews. Neurology, 2016)
The central vein sign (CVS) has been proposed as a novel MRI biomarker to improve the accuracy and speed of multiple sclerosis (MS) diagnosis. This Consensus Statement from the NAIMS Cooperative provides a roadmap to help radiologists and neurologists to better understand, refine, standardize and evaluate the CVS in the diagnosis of MS. Over the past few years, MRI has become an indispensable tool for diagnosing multiple sclerosis (MS). However, the current MRI criteria for MS diagnosis have imperfect sensitivity and specificity. The central vein sign (CVS) has recently been proposed as a novel MRI biomarker to improve the accuracy and speed of MS diagnosis. Evidence indicates that the presence of the CVS in individual lesions can accurately differentiate MS from other diseases that mimic this condition. However, the predictive value of the CVS for the development of clinical MS in patients with suspected demyelinating disease is still unknown. Moreover, the lack of standardization for the definition and imaging of the CVS currently limits its clinical implementation and validation. On the basis of a thorough review of the existing literature on the CVS and the consensus opinion of the members of the North American Imaging in Multiple Sclerosis (NAIMS) Cooperative, this article provides statements and recommendations aimed at helping radiologists and neurologists to better understand, refine, standardize and evaluate the CVS in the diagnosis of MS.